Cody

Solution 2036292

Submitted on 26 Nov 2019 by Asif Newaz
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

Test Suite

Test Status Code Input and Output
1   Pass
x = [1 0; 1 1]; y_correct = true; assert(isequal(fnt(x),y_correct))

a = 2 z = 0 0 0 0 z = 1 0 0 0 z = 1 0 1 0 z = 1 0 1 1 y = 1

2   Pass
x = [1 0 0; 1 1 0; 1 2 1]; y_correct = true; assert(isequal(fnt(x),y_correct))

a = 3 z = 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 0 0 0 0 z = 1 0 0 1 0 0 0 0 0 z = 1 0 0 1 1 0 0 0 0 z = 1 0 0 1 1 0 1 0 0 z = 1 0 0 1 1 0 1 2 0 z = 1 0 0 1 1 0 1 2 1 y = 1

3   Pass
x = [1 0 0 0; 1 1 0 0; 1 2 1 0; 1 3 3 1]; y_correct = true; assert(isequal(fnt(x),y_correct))

a = 4 z = 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 1 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 1 1 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 1 1 0 0 1 0 0 0 0 0 0 0 z = 1 0 0 0 1 1 0 0 1 2 0 0 0 0 0 0 z = 1 0 0 0 1 1 0 0 1 2 1 0 0 0 0 0 z = 1 0 0 0 1 1 0 0 1 2 1 0 1 0 0 0 z = 1 0 0 0 1 1 0 0 1 2 1 0 1 3 0 0 z = 1 0 0 0 1 1 0 0 1 2 1 0 1 3 3 0 z = 1 0 0 0 1 1 0 0 1 2 1 0 1 3 3 1 y = 1

4   Pass
x = [1 0 1; 1 1 0; 1 2 1]; y_correct = false; assert(isequal(fnt(x),y_correct))

a = 3 z = 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 0 0 0 0 z = 1 0 0 1 0 0 0 0 0 z = 1 0 0 1 1 0 0 0 0 z = 1 0 0 1 1 0 1 0 0 z = 1 0 0 1 1 0 1 2 0 z = 1 0 0 1 1 0 1 2 1 y = 0

5   Pass
x = zeros(5); y_correct = false; assert(isequal(fnt(x),y_correct))

a = 5 z = 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 1 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 0 0 0 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 0 0 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 0 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 1 0 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 1 3 0 0 0 0 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 1 3 3 0 0 0 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 1 3 3 1 0 0 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 1 3 3 1 0 1 0 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 1 3 3 1 0 1 4 0 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 1 3 3 1 0 1 4 6 0 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 1 3 3 1 0 1 4 6 4 0 z = 1 0 0 0 0 1 1 0 0 0 1 2 1 0 0 1 3 3 1 0 1 4 6 4 1 y = 0

Suggested Problems

More from this Author23